Geography Matters in Ancient Rome - Melanie Waldron (Oxford, United Kingdom Capstone Global Library Ltd, 2015)
Why did Roman towns have bathhouses? Why was Rome at great risk from fires? What happened to the town of Pompeii in AD 79? Geography Matters in Ancient Rome looks at how the Roman Empire changed through time and gives fascinating insights into many different aspects of Roman life through its geography. Read about how the Romans invented new farming methods such as a harvesting machine called a vallus, how some women in the Roman Empire had more freedom than in other civilizations, even running their husbands' businesses for them when they were away, and how the Empire was strengthened by the fact that the different climates, soils and terrain produced a huge range of goods and resources.
Keywords: Non Fiction -- Non Fiction